2021
DOI: 10.1037/rep0000379
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and blood pressure in individuals aging with traumatic brain injury.

Abstract: Purpose/Objective: Older adults with a history of traumatic brain injury (TBI) remain an understudied population, resulting in a paucity of geriatric-specific guidelines. Given an increased vascular risk among older adults with TBI, we aimed to examine distal predictors of vascular health in this population. Specifically, we sought to compare levels of perceived discrimination in Black and White older adults with a history of complicated mild, moderate, or severe TBI, and to examine the relationship between le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The present study builds on our previous findings in older individuals with chronic moderate-to-severe TBI (>1 year postinjury) 21 by expanding the investigation of MED and EED to behavioral health. Our principal research questions were as follows: (1) "What are the relationships between perceived discrimination and behavioral health outcomes in older PwTBI?"…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…The present study builds on our previous findings in older individuals with chronic moderate-to-severe TBI (>1 year postinjury) 21 by expanding the investigation of MED and EED to behavioral health. Our principal research questions were as follows: (1) "What are the relationships between perceived discrimination and behavioral health outcomes in older PwTBI?"…”
mentioning
confidence: 76%
“…The present study builds on our previous findings in older individuals with chronic moderate-to-severe TBI (>1 year postinjury)21 by expanding the investigation of MED and EED to behavioral health. Our principal research questions were as follows: (1) “What are the relationships between perceived discrimination and behavioral health outcomes in older PwTBI?” and (2) “Are these relationships independent of demographic and clinical factors?” On the basis of literature in non-TBI samples, we hypothesized that greater perceived discrimination would be related to poorer patient-reported behavioral outcomes and cognitive performance and that these relationships would be independent of age, sex, race, education level, injury severity, and time postinjury (ie, injury chronicity).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…A study showed that racial/ethnic minority patients had poorer communication experiences pertaining to their health care 52 . Lack of awareness of one’s own biases (particularly related to race/ethnicity) among healthcare providers, as well as lack of strategies to overcome these biases, can negatively impact decision making related to TBI, directly influencing decisions on discharge destinations, treatments, and referrals and indirectly influencing mortality and other outcomes 53 . To close the gap in the literature on existing health disparities in the TBI population, the purpose of this analysis and perspective is to provide recommendations for further examination of subjective factors in research and practice that would help identify strategies to improve clinical practice with the overarching goal of reducing TBI-related disparities.…”
mentioning
confidence: 99%